Lending Booms, Real Estate Bubbles and the Asian Crisis - Senhadji, Abdelhak (IMF Working Papers; Working Paper ;, 2002)
This paper examines the link between lending booms, asset price cycles, and financial crises across East Asian countries. Both theoretical arguments and empirical evidence support a strong relationship between bank lending and asset price inflation, especially in the real estate market. While asset price bubbles were present in most Asian countries during the 1990s, their subsequent bust has affected countries quite differently. Some countries underwent severe exchange and financial crises, while others were able to weather the storm with much less damage. This experience underlines the importance of a strong bank regulatory system.